2019
DOI: 10.3102/0002831219883237
|View full text |Cite
|
Sign up to set email alerts
|

Summer Credit Recovery Impact on Newcomer English Learners

Abstract: Prior research shows that English learners (ELs) lag behind their peers in academic achievement and education attainment. The persisting gap is partly attributed to ELs’ limited exposure to academic content. This article investigates the efficacy of a summer credit recovery program aimed at expanding high school newcomer ELs’ access to academic subjects. Leveraging student-level data from a large urban district in California, I use a difference-in-differences-in-differences approach to estimate the program’s i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…In order to help students maintain and continue to develop the language and academic skills they gained during the school year, schools and communities might consider offering programs during summers and other out-of-school time. Research has shown targeted summer programs of extensive duration to have positive effects on academic outcomes for high school newcomer ELs (Johnson, 2020b) and elementary school students from socioeconomically-disadvantaged families (Augustine et al, 2016). Experts in research and practice might consider designing programs that would expand learning opportunities beyond the academic year for current-ELs and dually-identified students.…”
Section: Discussionmentioning
confidence: 99%
“…In order to help students maintain and continue to develop the language and academic skills they gained during the school year, schools and communities might consider offering programs during summers and other out-of-school time. Research has shown targeted summer programs of extensive duration to have positive effects on academic outcomes for high school newcomer ELs (Johnson, 2020b) and elementary school students from socioeconomically-disadvantaged families (Augustine et al, 2016). Experts in research and practice might consider designing programs that would expand learning opportunities beyond the academic year for current-ELs and dually-identified students.…”
Section: Discussionmentioning
confidence: 99%
“…By targeting schools in these areas, the programmes aim to provide educational opportunities to underperforming students who may otherwise have limited access to academic support. This can include learners of English as a second language or students who have been grade retained or are at risk of grade retention (the practice in the US whereby students repeat a grade level) (Johnson, 2020 ; Mariano & Martorell, 2013 ).…”
Section: Design Features Of Summer Programmes and Their Theories Of C...mentioning
confidence: 99%
“…There does not appear to be any significant impact on reading and writing scores . Three of the four studies evaluating both outcomes find larger effects or impacts on writing than reading scores: reading skills may tend to develop more gradually compared to writing skills, and therefore summer programme's short duration may not allow sufficient time for as considerable an improvement in this skill (Johnson, 2020 ). The findings relating to reading and writing scores are low‐confidence.…”
Section: Impact Of Summer Programmesmentioning
confidence: 99%
See 2 more Smart Citations